Sistem Pakar SISTEM PAKAR DIAGNOSA PENYAKIT TANAMAN KARET BERBASIS ANDROID DENGAN METODE FORWARD CHAINING - Imron, Ali; Qisthiano, M Riski (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2024)
The expert system for diagnosing rubber plant diseases is a system that works based on a collection of facts obtained from a rubber plant expert, from a collection of these facts it will be concluded as an answer to the existing facts. The system for finding conclusions from these facts uses an inference system in the form of forward chaining whose working system uses a rule base. The rule base consists of if and then, where if contains a collection of existing facts while then is a conclusion of the facts contained in if. The conclusion contained in then will be displayed as the result of the diagnosis in the expert system application for diagnosing rubber plant diseases based on android with the forward chaining method. The results of the conclusion of these facts can be used as an initial diagnosis of rubber plant diseases